O pequeno concerto para violino e cordas de Edino Krieger: estudo do estilo e autoetnografia da performance com ênfase na expressividade musical - Furtado, Fernanda Lúcia Acioli (2021)
This research aims at understanding in which ways musical style and autoethnography can contribute to the construction of the performance of the piece Pequeno Concerto para Violino e Cordas by Edino Krieger. Therefore, I present a theoretical framework with a concept of style and performance autoethnography. Therefore, in this artistic research, I use the study of style and performance autoetnography as part of the methodology. Integrating the study of style, I offer a brief biography of the composer and also a contextualization and analysis of the piece, using pitch-class set theory. I then present a few performances available in digital platforms and some of their contributions to the consolidation of the piece’s style. After that, I present my own path as a performer and a reflection about the performance of the digital concert that I published on YouTube, which I comment in brief demonstrations of bits of the Pequeno Concerto. This research is justified by the importance of the performer’s point of view in the artistic creation of a musical work, because the autoetnography makes explicit the practical processes involved in a performance. I then emphasize the relevance studying style and the process of performance autoetnography in the construction of the piece through musical expressiveness. In the final considerations I reinforce that each performer is unique and influences other performers in the consolidation of a musical style. Therefore, this research can serve so that the academic community can reflect on the complexities of creative processes in performance.